If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (b + -5)(2b + -1) = 0 Reorder the terms: (-5 + b)(2b + -1) = 0 Reorder the terms: (-5 + b)(-1 + 2b) = 0 Multiply (-5 + b) * (-1 + 2b) (-5(-1 + 2b) + b(-1 + 2b)) = 0 ((-1 * -5 + 2b * -5) + b(-1 + 2b)) = 0 ((5 + -10b) + b(-1 + 2b)) = 0 (5 + -10b + (-1 * b + 2b * b)) = 0 (5 + -10b + (-1b + 2b2)) = 0 Combine like terms: -10b + -1b = -11b (5 + -11b + 2b2) = 0 Solving 5 + -11b + 2b2 = 0 Solving for variable 'b'. Factor a trinomial. (1 + -2b)(5 + -1b) = 0Subproblem 1
Set the factor '(1 + -2b)' equal to zero and attempt to solve: Simplifying 1 + -2b = 0 Solving 1 + -2b = 0 Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2b = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2b = 0 + -1 -2b = 0 + -1 Combine like terms: 0 + -1 = -1 -2b = -1 Divide each side by '-2'. b = 0.5 Simplifying b = 0.5Subproblem 2
Set the factor '(5 + -1b)' equal to zero and attempt to solve: Simplifying 5 + -1b = 0 Solving 5 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1b = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1b = 0 + -5 -1b = 0 + -5 Combine like terms: 0 + -5 = -5 -1b = -5 Divide each side by '-1'. b = 5 Simplifying b = 5Solution
b = {0.5, 5}
| 5(x+1)-x=4x+5 | | Y(9+y)=y*9+y*y | | -(2n+2n)= | | n+1n-5=0 | | 6i(4+2i)= | | 12x^2+3x-144=0 | | 5x-2(0)=9 | | p-4p+3=0 | | 6x^2+3x-144=0 | | 7(3y-6)=21 | | -10-5x^2=-350 | | k/-9=(-9) | | X*15=4 | | p/(-3)=(-10) | | 5(-4)-2y=9 | | 2x+6x-45=9 | | -2x-32=4(x+5)-4 | | 3x+7=4(2x-2) | | 2a-3(a-5)=5 | | k-(-71)=74 | | c-78=(-10) | | 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 |